2014
DOI: 10.1007/s12155-014-9521-x
|View full text |Cite
|
Sign up to set email alerts
|

Ploidy Level Affects Important Biomass Traits of Novel Shrub Willow (Salix) Hybrids

Abstract: Polyploidy is a common observation in the genus Salix, including some of the shrub willow species currently being bred as a potential bioenergy feedstock. Breeding of shrub willow has produced new species hybrids, among which a disproportionate number of high-yielding genotypes are triploid, produced from crosses between diploid and tetraploid parents. These novel hybrids display significant variation in biomass compositional quality, including differences according to ploidy. The triploid and tetraploid genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 35 publications
3
47
1
Order By: Relevance
“…The stems of S. psammophila require flat stubble once every 3–5 years to allow growth to flourish and its branch residues contain high cellulose, hemicellulose and lignin contents of 55.45%, 18.98% and 25.98%, respectively89. The cellulose content of S. psammophila is higher than those reported in the study of Serapligia et al 10,. which included 75 diploid, triploid and tetraploid shrub willows with cellulose content ranging from 39.9% to 46.64%.…”
mentioning
confidence: 72%
“…The stems of S. psammophila require flat stubble once every 3–5 years to allow growth to flourish and its branch residues contain high cellulose, hemicellulose and lignin contents of 55.45%, 18.98% and 25.98%, respectively89. The cellulose content of S. psammophila is higher than those reported in the study of Serapligia et al 10,. which included 75 diploid, triploid and tetraploid shrub willows with cellulose content ranging from 39.9% to 46.64%.…”
mentioning
confidence: 72%
“…Recently, Serapiglia et al . demonstrated that triploid shrub willows produced higher biomass yield than their diploid and tetraploid parents23. As in many plants, polyploid breeding is also a highly desirable means for breeding elite willow cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…These novel hybrids display significant variation in biomass production. Significant difference has been observed between ploidy level and growth in some willow species23. In general, triploid willows are more vigorous and produce higher yield than their diploid and tetraploid parents2425, and it has been demonstrated that the triploid and tetraploid willows possessed lower lignin content than the diploid genotypes23.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall aim of the sustainable and economically efficient biomass conversion is to provide a biomass feedstock with optimized properties, best suited for further downstream conversion. Improvements in total biomass yield, biomass quality, and biomass energy content must be matched with the conversion process for which the willow is grown as a feedstock (Serapiglia et al 2015). Various aspects of the biomass quality could be of interest depending on the desired end-use.…”
Section: Introductionmentioning
confidence: 99%